Pengaruh Pengembangan Karir Dan Kedisiplinan Yang Dimoderasi Oleh Reward Terhadap Kinerja Karyawan Informa Queen City Semarang - Anistia Dewi Muflikhah; Bayu Kurniawan; Rita Meiriyanti (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
Human Resources are the main calculation in achieving organizational goals strongly and efficiently. Organizations must be able to carry out supervision well to achieve ideal business implementation. Every organization generally expects achievements from its representatives because the organization is given the authority to make presentations. The aim of this research is to find out and analyze whether career development and discipline moderated by rewards have an effect on the performance of Informa Queen City Semarang employees. The method used is a quantitative method. The data collection techniques used were literature and questionnaires. The results of this research are that career development has no effect on the performance of Informa Queen City Semarang employees, discipline has a positive effect on the performance of Informa Queen City Semarang employees, career development and discipline simultaneously influence employee performance through rewards.